THE THEORY OF AUTOCHTONOUS ZIONISM IN POLITICAL DISCOURSES IN ISRAEL 1961-1967 - Haramati, Michal (Journal of Tourism, Sustainability and Well-being, 2018)
The premise of this investigation conceives of Western colonization as the central factor shaping modern history and contemporary geopolitics. In a local context, it perceives of the Zionist project from its inception as colonial, created by European Jews, supported by western powers and based upon perceived civilizational supremacy of western modernity. The Zionist movement affected not only the fate of Palestinian Arabs, but also the native Jewish population and Jewish migrants from Muslim countries to Eretz Israel/Palestine. This research follows political organizations consisting of non-European Jews, autochthonous in the Middle Eastern region, named here Oriental and Sephardic Jews. This research examines Sephardic and Oriental political debates that resisted the colonial postulates of the Zionist state. First, the genealogy of these debates since the beginning of Zionist settlement at the end of the 19th century is presented. This is followed by a description of the fragmentation that the establishment of the state of Israel, as a European enclave in its region, caused these autochthonous Jews. Together these elements form the historical layout of sociological inquiry into a particular discourse of autochthonous Zionism in the 1960s, as it developed on the pages of “In the Battle”, a cultural-political journal.